Myomectomy during caesarian section: a case report - Dhungana, Rakshya (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Leiomyomas are the most common benign tumors with an incidence of 2 to 4% of the reproductive tract in women of childbearing age. Myomectomy is the most common surgical operation performed. In a study that reviewed 10 years of experience in doing myomectomy during the cesarian section, about 0.89% had myomectomy. Although the Caesarean myomectomy rate is currently increasing, many doctors are reluctant to perform Caesarean myomectomy, due to potential associated risks, particularly the perioperative hemorrhage. It has been documented that a single CM is associated with a higher rate of bleeding when the leiomyoma diameter is more than 75 mm. We reported the case of a 26-year primigravida at 38 weeks of gestation who presented with pervaginal leaking and pain in the abdomen. We found she had a huge mass over the posterior wall of the uterus. A Caesarean myomectomy was performed. Histopathologically it was proven to be a fibroid uterus.